Identify and validate a novel ubiquitination-related biomarker for thyroid cancer prognosis and immunotherapy - Li, Yilin; Zeng, Jutao; Gong, Xiongmeiyu; Li, Wei; Liu, Jueli; Li, Dan; Zhong, Yangyan; Deng, Junjie; Deng, Jian; Feng, Haigang; Luo, Jie; Cao, Hong (Frontiers in Oncology, 2026)
BackgroundUbiquitination is a critical protein modification process that plays a pivotal role in maintaining cellular homeostasis and is implicated in various pathophysiological processes, including thyroid cancer (THCA). Understanding the roles of ubiquitination-related genes in THCA progression and their interactions with the tumor microenvironment (TME) could provide valuable insights into prognosis and treatment strategies.MethodsUsing iUUCD 2.0, ubiquitination-related genes were identified and subjected to consensus clustering on TCGA-THCA data. Differentially expressed genes (DEGs) between tumor and normal tissues were identified and used to construct a ubiquitination-related signature using Cox and LASSO regression. The signature’s prognostic ability was validated using training and test datasets from TCGA. Immune cell infiltration, immunotherapy response, and drug sensitivity were analyzed.ResultsThree ubiquitination clusters were identified among 454 genes. Four prognostic DEGs (F12, FBXO15, FBXW10, and USP44) formed the signature, significantly correlating with survival, immune cell infiltration, clinical characteristics, immune checkpoints, immunotherapy response, and drug sensitivity. Low-risk THCA patients had better prognosis and immunotherapy responses than high-risk patients. A stable nomogram combining the signature and clinical characteristics predicted patient survival. RT-qPCR and immunohistochemistry confirmed differential expression of key genes.ConclusionOur study identifies and validates a novel four-gene ubiquitination-related signature as a promising and independent prognostic biomarker in THCA. Beyond outcome prediction, this signature demonstrates significant translational potential by accurately predicting immunotherapy responses, thereby facilitating the development of more personalized and effective treatment strategies for patients with THCA.